2008
DOI: 10.1590/s1679-62252008000300021
|View full text |Cite
|
Sign up to set email alerts
|

Platydoras brachylecis, a new species of thorny catfish (Siluriformes: Doradidae) from northeastern Brazil

Abstract: Platydoras brachylecis, new species, is described from coastal drainages of northeastern Brazil (Pindaré to Parnaíba rivers), and diagnosed from congeners by the unique combination of: pale yellow to white stripe beginning above orbits, continuing midlaterally on body and onto middle rays of caudal fin; skin in axil of each midlateral thorn without concentration of pigment forming small dark spot, midlateral scutes shallow (depth of 10 th scute 8.8-11.9% of SL), and midlateral scutes on caudal peduncle distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 7 publications
(4 reference statements)
0
11
0
4
Order By: Relevance
“…This previously defined northeastern Brazil endemic region has now been split into three regions corresponding to the Maranhão River, the Parnaíba River Basin and coastal rivers north of the São Francisco River (Lundberg et al, 1998). In recent years, new fish species have been described in this region (Piorski et al 2008;Triques, 1999;Ferraris and Vari, 1999).…”
Section: Fish Community Structure and Hydrographic Basinsmentioning
confidence: 99%
“…This previously defined northeastern Brazil endemic region has now been split into three regions corresponding to the Maranhão River, the Parnaíba River Basin and coastal rivers north of the São Francisco River (Lundberg et al, 1998). In recent years, new fish species have been described in this region (Piorski et al 2008;Triques, 1999;Ferraris and Vari, 1999).…”
Section: Fish Community Structure and Hydrographic Basinsmentioning
confidence: 99%
“…Other recent studies have demonstrated a low level of knowledge on the taxonomy of the Parnaíba River ichthyofauna. For example, Staeck & Shindler (2006) described Geophagus parnaibae based on specimens traditionally identified as G. surinamensis; Piorski et al (2008) described Platydoras brachylecis based on specimens identified as P. costatus. The aim of this study was to describe the diversity of freshwater fishes of the Parnaíba River basin through an extensive inventory.…”
Section: Introductionmentioning
confidence: 99%
“…Two years later, Birindelli et al (2007) described Rhynchodoras castilloi from Venezuela; Higuchi et al (2007) described a new genus and species, Merodoras nheco; and Sabaj Pérez et al (2007) described †Doras dionae, the only named fossil species. In 2008, described two new species of Rhinodoras; revised Doras, describing three species as new; described Leptodoras oyakawai; and Piorski et al (2008) described Platydoras brachylecis and revalidated P. hancockii. Two years later, Birindelli & Sousa (2010) described Leptodoras marki.…”
mentioning
confidence: 99%